Judicial policy, public perception, and the science of decision making: A new framework for the law of apprehended bias - Higgins, A; Levy, I (Sweet and Maxwell, 2018)
The right to an impartial and independent tribunal is fundamental to the administration of justice and public confidence in it. However, the test for apprehended bias is not informed by psychological research on cognitive biases, and while courts purport to give effect to the views of a fair-minded and informed member of the public on the risk of bias, little attention has been given to what the public thinks in reality. Using doctrinal analysis and drawing on psychological literature, the article argues that the law must be re-examined with a view to closing the gap between the case law on which factors give rise to a reasonable risk of bias, public attitudes, and psychological research on decision-making. The article proposes a new framework for the law of bias, including a judicial code that identifies circumstances when judges should and should not sit based on legal policy considerations, measured public opinion, and relevant psychological studies, and new procedures and tests for courts dealing with cases that are not identified as automatic disqualification or non-disqualification scenarios under a code.